Academic degree recognition in a global era: The case of the doctorate of education (EdD) in Israel. (27th March 2018) - Bamberger, Annette
Abstract : The current discussion around recognition of the doctorate of education (EdD) typically focuses on a national context, usually in relation to the PhD; however, relatively little is known about recognition of the EdD degree in countries that do not offer the qualification. As international cohorts and online delivery of doctoral education grows, it is valuable to understand the recognition of the EdD, particularly in countries that do not currently offer it, and in which policy and legislation may impede its recognition. Using Israel as a case, this study explores EdD recognition in a country that does not offer the degree and that has a particularly rigid recognition system, likely as a result of a neoliberal experiment with the deregulation of the higher education arena in the 1990s. My investigations indicate three spheres of recognition for the degree: the public, private and academic spheres. This article outlines these spheres and explores the implications of such a system.